2022
DOI: 10.21608/ejoh.2022.137703.1200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Spraying with Different Sources of Potassium on Growth, Leaf Mineral Composition, Yield and Fruit quality of Picual Olive Trees.

Abstract: Picual olive trees grown in a private orchard located 182 kilometers south of Cairo on the Western Desert Road in Minia Governorate, and aimed to investigate the effect of foliar sprays with different potassium sources on growth, leaf mineral composition, yield and fruit quality. Foliar application potassium sources such as; potassium sulfate, potassium nitrate, potassium citrate and monopotassium phosphate were applied at 1.5 % and 3 % . Spraying is carried out three times immediately after the final fruit se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Number of fruits per plant: Gowda and Gowda (1983) stated that chlormequat chloride increased the number of fruits per plant in okra. Rathod and Patel (1996) also reported that chlormequat treatments resulted in the highest number of fruits per plant in okra.…”
Section: Treatmentsmentioning
confidence: 99%
“…Number of fruits per plant: Gowda and Gowda (1983) stated that chlormequat chloride increased the number of fruits per plant in okra. Rathod and Patel (1996) also reported that chlormequat treatments resulted in the highest number of fruits per plant in okra.…”
Section: Treatmentsmentioning
confidence: 99%